Effort to Improve Reading Comprehension Skills Through the Know Want Learned Model in Elementary School Student - Rahma Maesaroh; Arsyi Rizqia Amalia; Luthfi Hamdani Maula (Papanda Publisher, 2026)
Reading comprehension is a fundamental skill in elementary education, yet many students struggle to grasp textual meaning. Initial observations in this study revealed a low classical completion rate of only 34% among Grade V students, primarily due to the dominance of passive conventional teaching methods. This study aims to describe the learning process and evaluate the improvement of reading comprehension skills through the implementation of the Know-Want-Learned (KWL) model. A Classroom Action Research (CAR) design was employed across two cycles, each consisting of planning, action, observation, and reflection. The research involved 5th-grade students, with data gathered via observation sheets, interviews, field notes, and comprehension tests. Results showed a significant upward trend in student performance and engagement. While Cycle I addressed initial instructional challenges, Cycle II demonstrated substantial progress where students successfully exceeded the 75% classical completeness threshold. By systematically activating prior knowledge (Know), establishing clear reading purposes (Want), and reflecting on acquired information (Learned), students became more engaged and critical in analyzing texts. The findings reveal that the KWL model not only improves comprehension scores specifically in identifying main ideas and summarizing but also enhances student motivation. In conclusion, the KWL model is a highly effective strategy for bridging the literacy gap in elementary education. This research implies that teachers should adopt structured, student-centered reading strategies like KWL to foster deeper cognitive engagement and transition away from monotonous traditional instruction, thereby significantly improving the quality of language learning.